The ‘Christian’ Ilkhans: myths and reality - Margaryan, Gor (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
The aim of this research is to discuss several peculiarities and influences from the religious factor on the internal policy of the Ilkhans, based on written sources. In this frame of reference, peculiarities and influences of the religious factor on the internal policy of Ilkhans are discussed on the basis of written sources. This article aims to study specific peculiarities of the Ilkhans’ religious policy in relation to subject religious communities dependent on the religious affiliation of the Ilkhans themselves, to discuss the issue of the religious affiliation of the Ilkhans, to analyze the phenomenon of the ‘Christianisation’ of the Ilkhans in written sources of the XIII-XV centuries (Armenian, Georgian, Syrian, and European) and to identify the very perception of the image of ‘Ilkhans of a Christian’ in the sources. The article does not include a study of the relations between the Ilkhans and the Christian West and the Roman Catholic Church. A number of studies are available on the relations of Mongolian khans (particularly the Ilkhans) with Christian Europe, on the religious policy of the papacy, and the attempts of the union of both sides against the Islamic world , and thus this topic is not covered here.